2007
DOI: 10.2202/1556-3758.1077
|View full text |Cite
|
Sign up to set email alerts
|

Drying Behaviour and Energy Requirement for Dehydration of White Onion Slices

Abstract: White onions were dried using an osmo-convective drying technique. Osmotic dehydration was done by dipping the onion slices in 10, 15 and 20 brix NaCl solution at ambient temperature for one hour. The increase in the concentration of NaCl increased the water loss, solid gain and weight reduction in onion slices. The drying times of pre-osmosed onions slices at drying air temperature of 50, 60 and 70°C were 6.75, 6.00 and 5.25 h respectively. The moisture diffusivity increased with increase in air temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Dewatered pulp has more surface area than slices (Mudahar et al 1990;EEBPP 1996;Madamba and Bekki 2001;BEE 2004, Kumar Parveen et al 2005Arabhosseini et al 2010;Aversa et al 2010), which aided in higher heat and mass transfer rate for the samples to be dried. The results corroborate with earlier findings (Vergara et al 1997;Sarsavadia et al 1999;Revaskar et al 2007) where osmotic dewatering prior to drying significantly affected the moisture curves. The drying temperature also affected total drying time (Fig.…”
Section: Effect Of Partial Mechanical Dewatering On Drying Characterisupporting
confidence: 92%
See 2 more Smart Citations
“…Dewatered pulp has more surface area than slices (Mudahar et al 1990;EEBPP 1996;Madamba and Bekki 2001;BEE 2004, Kumar Parveen et al 2005Arabhosseini et al 2010;Aversa et al 2010), which aided in higher heat and mass transfer rate for the samples to be dried. The results corroborate with earlier findings (Vergara et al 1997;Sarsavadia et al 1999;Revaskar et al 2007) where osmotic dewatering prior to drying significantly affected the moisture curves. The drying temperature also affected total drying time (Fig.…”
Section: Effect Of Partial Mechanical Dewatering On Drying Characterisupporting
confidence: 92%
“…Thus mechanical dewatering prior to hot air drying had profoundly affected energy consumption. On similar lines, Revaskar et al (2007) had also reported marginal decrease in energy consumption by drying pre-osmosed onion slices due to partial removal of water from the product before drying. Drying air temperature worked synergistically with the predewatering treatment in reducing the energy consumption (Koyuncu et al 2004).…”
Section: Effect Of Partial Mechanical Dewatering On Specific Energy Cmentioning
confidence: 78%
See 1 more Smart Citation
“…A fit of the moisture content curves versus time to a first order kinetics is also carried out. This model is known as a simple model (exponential) whose mathematical expression is (Krokida et al, 2003;Senadeera et al, 2003;Simal et al, 2005;Vega-Gálvez et al, 2008):…”
Section: Methodsmentioning
confidence: 99%
“…The physical, texture and nutritional characteristics of food products are modified due to heat treatments (Krokida et al, 2000a,b). In this regard, the osmotic treatments, previous to air-drying process (Lewicki et al, 2002;Rastogi et al, 2004;Revaskar et al, 2007) improve the nutritional, sensory and functional characteristics of dehydrated food products. They may even improve the texture and the stability of pigments during the dehydration and storage of dehydrated products.…”
Section: Introductionmentioning
confidence: 99%